Quality assessment of systematic reviews of the significance of keratinized mucosa on implant health. Issue 6 (June 2017) - Moraschini, V.; Luz, D.; Velloso, G.; Barboza, E.dS.P.
Abstract: The aim of this overview was to assess the methods, quality, and outcomes of systematic reviews conducted to evaluate the importance of keratinized mucosa (KM) for the maintenance of peri-implant tissue health in humans. An electronic search was conducted without date or language restriction using the MEDLINE/PubMed, Cochrane Library, Web of Science, and Embase databases up to December 2015. The eligibility criteria included systematic reviews with/without meta-analysis and with a focus on the influence of KM on peri-implant health around implants. Two independent authors performed the quality analysis of the reviews with the AMSTAR guidelines and another checklist proposed in 2003. After screening, four systematic reviews were selected. The present study demonstrated the existence of structural and methodological variability among the systematic reviews with/without meta-analysis. None of the systematic reviews that were included in the study obtained the maximum score in the two quality analyses performed. All systematic reviews included reported a positive association between an adequate KM width (≥2 mm) and peri-implant health. There is still insufficient data on the long-term survival and success rates of dental implants. Prospective studies evaluating the importance of KM for the long-term maintenance of dental implants are needed.